Supporting MSMEs: Assisting Local Entrepreneurs in Facing Modern Market Challenges - Sari, Devit Etika; Indrasari, Meithiana; Pamuji, Eko; Prasnowo, M. Adhi (Bisma : Bimbingan Swadaya Masyarakat, 2024)
This community service program was designed to enhance the teaching competence of elementary school teachers in Bangkalan Regency by introducing them to the use of Science City learning media. The training aimed to address the lack of innovation and creativity in classroom practices, equipping teachers with the skills to incorporate interactive media into their lessons. The results demonstrated that the training successfully improved the teachers' ability to use educational media, increased their creativity in lesson delivery, and boosted student motivation and engagement. The program also encouraged teachers to explore new teaching strategies, ensuring a more student-centered learning environment. Moving forward, the program's continuation is expected to foster further innovation in teaching, ultimately leading to improved student learning outcomes. This initiative highlights the importance of integrating media into the teaching process as a means of enhancing both teaching practices and educational quality.